2010
DOI: 10.1007/s00405-010-1404-y
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin expression and sensitivity in otosclerosis with different histological activity

Abstract: Otosclerosis is a complex bone dystrophy of the human otic capsule leading to conductive and sensorineural hearing loss. Since otosclerosis may, at least in part, be considered as an autoimmune-inflammatory disease, disturbed balance of TNF-alpha and osteoprotegerin (OPG) expression has been implicated in the pathological bone remodeling. It has been supposed that active otosclerosis is characterized by decreased or missing local OPG production with invariable OPG sensitivity of the otosclerotic foci. Ankyloti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…OPG, RANK, and RANKL mRNA was detected with 100% effectiveness in the specimens from cadavers and incus bones applied as negative controls for OTSC. The result of our finding is in accordance with the previous report which detected the OPG mRNA expression in all the cortical bone fragments applied as negative controls for OTSC (Karosi et al, 2011). Based on the established role of OPG as a powerful inhibitor of bone remodeling, our finding indicates that detectable OPG expression in all the normal tissue may be an important factor for normal bone remodeling in the otic capsule.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…OPG, RANK, and RANKL mRNA was detected with 100% effectiveness in the specimens from cadavers and incus bones applied as negative controls for OTSC. The result of our finding is in accordance with the previous report which detected the OPG mRNA expression in all the cortical bone fragments applied as negative controls for OTSC (Karosi et al, 2011). Based on the established role of OPG as a powerful inhibitor of bone remodeling, our finding indicates that detectable OPG expression in all the normal tissue may be an important factor for normal bone remodeling in the otic capsule.…”
Section: Discussionsupporting
confidence: 83%
“…Gene expression profiling of disease tissue compared to controls has been suggested as a method to investigate the genetic basis of complex disorders (Xiong et al, 2012). Some of the studies have reported reduced or missing OPG expression in the otosclerotic tissue (Karosi et al, 2011;Potocka-Baklazec et al, 2014) but the exact mechanism that controls the altered OPG expression in OTSC is unclear. In this study, we aimed to identify the genetic risk factors in the OPG gene and to evaluate their potential role in OTSC development.…”
Section: Discussionmentioning
confidence: 99%
“…While conductive hearing loss in some OPG-related disorders can be attributed, at least in part, to abnormal function of middle-ear bones that transmit acoustic vibrations to the inner ear (Whyte et al, 2002; Daroszewska and Ralston., 2006), mechanisms of sensorineural hearing loss in these disorders are poorly understood (Bahmad and Merchant, 2007; Karosi et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Diffusion of OPG from the perilymph into the surrounding bone is intensive. Probably, this is one of the reasons why the otic capsule is unique in its morphology and development [ 60 ].…”
Section: Remodeling In Normal and In Otosclerotic Bonementioning
confidence: 99%